2014
DOI: 10.1038/oncsis.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 controls metastasis of androgen-independent prostate cancer cells through PXN and LPAR6

Abstract: Lysine-specific demethylase 1 (LSD1) was shown to control gene expression and cell proliferation of androgen-dependent prostate cancer (PCa) cells, whereas the role of LSD1 in androgen-independent metastatic prostate cancer remains elusive. Here, we show that depletion of LSD1 leads to increased migration and invasion of androgen-independent PCa cells. Transcriptome and cistrome analyses reveal that LSD1 regulates expression of lysophosphatidic acid receptor 6 (LPAR6) and cytoskeletal genes including the focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…PCa cells express several stem cell biomarkers, such as LSD1, SOX2, CD44, and CD133. [28][29][30][31][32] LSD1 and its inhibitor have been reported to target CSC markers in several cancers. 33,34 Sehrawat et al showed that LSD1 promotes PCa cell survival by activating gene networks that regulate the stem cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…PCa cells express several stem cell biomarkers, such as LSD1, SOX2, CD44, and CD133. [28][29][30][31][32] LSD1 and its inhibitor have been reported to target CSC markers in several cancers. 33,34 Sehrawat et al showed that LSD1 promotes PCa cell survival by activating gene networks that regulate the stem cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LSD1 inhibitors have been shown to inhibit the growth of teratocarcinoma, embryonic carcinoma, and seminoma cells (44). On the other hand, LSD1 depletion increased migration and invasion of androgenindependent prostate cancer cells (52). The dichotomy of this "Janus" effect (53) bears relevance given the nonuniform pharmacologic distribution of therapeutic agents within tumors (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been demonstrated to affect AR-mediated transcription such as epigenetic modifications, pioneer factors, and chromatin accessibility 9,12 . Demonstrating the importance of these coactivators and pioneer factors, FOXA1, HOXB13, GATA2, and KDM1A have been shown to be critical for AR signaling and are required for the growth of PCa cell lines [13][14][15][16] . In addition to initiating PCa growth, there is also evidence that AR signaling is associated with DNA damage.…”
mentioning
confidence: 99%